Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/diseases9020028
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic Therapy: Albumin-Binding Proteins Could Mediate Mechanisms Underlying the Accumulation of Small Molecule Receptor Tyrosine Kinase Inhibitors in Normal Tissues with Potential Harmful Effects on Health

Abstract: Anti-angiogenics currently used in cancer therapy target angiogenesis by two major mechanisms: (i) neutralizing angiogenic factors or their receptors by using macromolecule anti-angiogenic drugs (e.g., therapeutic antibodies), and (ii) blocking intracellularly the activity of receptor tyrosine kinases with small molecule (Mr < 1 kDa) inhibitors. Anti-angiogenics halt the growth and spread of cancer, and significantly prolong the disease-free survival of the patients. However, resistance to treatment, insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…This hypothesis believes that only free unbound drug from plasma (not plasma protein bound drug) can distribute to disease-targeted tissues to interact with its molecular target; while free drug exposure in the plasma would be similar to the disease-targeted tissues at steady state 41 , 42 ; and thus drug exposure in the plasma can be used to predict the pharmacodynamic effect of the drug candidate. However, this “free drug” hypothesis may only apply to a limited class of drug candidates but not applicable to many other compounds since many factors can cause an asymmetric free drug distribution between plasma and tissue 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 . Therefore, drug exposure in the plasma, without knowing the exposure in disease-targeted tissue/normal tissues, may mislead the selection of drug candidate to clinical trials 51 , 52 , 53 , 65 .…”
Section: What Are the Successful Strategies To Improve Each Aspect Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis believes that only free unbound drug from plasma (not plasma protein bound drug) can distribute to disease-targeted tissues to interact with its molecular target; while free drug exposure in the plasma would be similar to the disease-targeted tissues at steady state 41 , 42 ; and thus drug exposure in the plasma can be used to predict the pharmacodynamic effect of the drug candidate. However, this “free drug” hypothesis may only apply to a limited class of drug candidates but not applicable to many other compounds since many factors can cause an asymmetric free drug distribution between plasma and tissue 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 . Therefore, drug exposure in the plasma, without knowing the exposure in disease-targeted tissue/normal tissues, may mislead the selection of drug candidate to clinical trials 51 , 52 , 53 , 65 .…”
Section: What Are the Successful Strategies To Improve Each Aspect Of...mentioning
confidence: 99%
“…In fact, albumin is actively transported from plasma to extra-cellular matrix, and to tissues through FcRn and other active transport process 45 , which carries fatty acids or drugs to different tissues. Previous study found that albumin-bound small molecules (tyrosine kinase inhibitors) interacting with albumin-binding proteins on vascular and in tissues, such as gp18, gp30, gp60/albondin, and secreted protein acidic and cysteine-rich (SPARC), which mediates tissue accumulation of these small molecules in normal tissues, which is associated with their toxicity 46 . Protein-bound drugs may also contribute higher drug accumulation in tumor tissues than that in the normal tissues 40 .…”
Section: How To Implement Star In Drug Optimization Process and Futur...mentioning
confidence: 99%
“…43 In addition to Oatp1b2 expression, 6DT1 tumors and cells express higher levels of proteins that uptake albumin, including secreted protein acidic and rich in cysteine (Sparc), compared to surrounding breast tissues (Table S2). 44,45 These expression data show that our 6DT1 model reflects expression trends found in human breast cancer and is therefore appropriate and clinically relevant for investigating Oatp-and albuminmediated cellular uptakes of cyanine organic salts.…”
Section: Counterion Tuning Of Organic Salts Controls Toxicity During ...mentioning
confidence: 66%